Histone Demethylase KDM4C Is Required for Ovarian Cancer Stem Cell Maintenance. (29th August 2020) - Chen, Guo-Qing; Ye, Ping; Ling, Rong-Song; Zeng, Fa; Zhu, Xiong-Shan; Chen, Lu; Huang, Yan; Xu, Ling; Xie, Xiao-Ying
Abstract : Ovarian cancer is a highly deadly disease, which is often diagnosed at a late stage with metastases. However, most ovarian cancers relapse after surgery combined with platinum-based chemotherapy. Cancer stem cells (CSCs) are stem-like cells that possess high tumorigenic capability and display higher resistant capability against current therapies. However, our knowledge of ovarian CSCs and their molecular mechanism remains sparse. In the current study, we found that KDM4C, a histone demethylase, was required for ovarian cancer stem cell (CSC) maintenance. Depletion of KDM4C significantly reduced the CSC population and sphere formation in vitro. Moreover, we found that KDM4C can regulate the expression of stem cell factor OCT-4 via binding to its promoter. These data indicate that KDM4C is relevant for ovarian CSC maintenance and underscore its importance as a potential therapeutic target.